DMSO‐Mediated Ligand Dissociation: Renaissance for Biological Activity of N‐Heterocyclic‐[Ru(η6‐arene)Cl2] Drug Candidates. Issue 44 (2nd October 2013) - Patra, Malay; Joshi, Tanmaya; Pierroz, Vanessa; Ingram, Katrin; Kaiser, Marcel; Ferrari, Stefano; Spingler, Bernhard; Keiser, Jennifer; Gasser, Gilles
<x xml:space="preserve">Abstract</x> Slipped under the radar? 1H NMR spectroscopic examination revealed that [Ru(η6‐arene)Cl2(L)] (L=N‐heterocyclic ligands) complexes readily undergo a ligand exchange reaction in DMSO (see scheme), a popular medium for preparing stock solutions for biological screening. It is therefore highly important for researchers to study the stability in DMSO before reporting on the biological activity of such complexes.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>